Breaking A World War I (WWI) Story from The Characters’ Point of View in Film “1917” - Fitriyah, Fitriyah; Mizola Revanza, Mario; Alawiyah, Sufi (Universitas Cokroaminoto Palopo, 2025)
A movie, also known as a film or motion picture, is a form of visual art used to entertain audience that can communicate ideas, stories, perceptions, feelings, or atmosphere through moving images. The aims of the research are to analyze the world war I story from the main character point of view from “1917”. This thesis aims to show readers how frightening war can be and how it differs from what is portrayed in the media. In order to gather information for this thesis, two ideas from Postcolonial Theory and Characterization as well as the movie